An Overview of Tropical Diseases - Samie, Amidou (IntechOpen, 2015)
Tropical diseases affect millions of people throughout the world and particularly in the developing countries. The millennium development goals had specifically targeted HIV/AIDS and Malaria for substantial reduction as well as Tuberculosis while many other tropical diseases have been neglected. The new sustainable development goals have not made such distinction and have targeted all diseases for elimination for the improvement of the quality of life of human beings on earth. The present book was developed to provide an update on issues relevant to the treatment of selected tropical diseases such as tuberculosis, malaria, leishmaniasis, schistosomiasis and ectoparasites such as chiggers which are widely distributed throughout the world. The control of these infections has been hampered by the development of drug resistance and the lack of the development of new and more effective drugs. The understanding of the biochemical processes underlying drug activity is therefore essential for the potential elimination of these infections.